Estimation of Adiponectin Hormone and Antioxidants Levels in Type 2 Diabetic Patients in Dhiqar Province - Ahmed Abdul Redha Jallod (Journal of Global Pharma Technology, 2016)
The present study was aimed to investigate the changes associated with type II diabetes in the level of adiponectin and antioxidants: (Catalase, Glutathione, Superoxide dismutase and Vitamin C). Seventy Samples (taken from male patients) were collected in cooperation with the Specialized Center for Diabetes and Endocrinology in the Directorate of Health in Thi-Qar Governorate. The numbers of healthy samples were 30. The results showed a significant decrease (P≤ 0.05) in the level of adiponectin and antioxidants (catalase, glutathione and vitamin C) in diabetic patients, while it was observed that there was a significant increase in the level of antioxidant superoxide dismutase in diabetic compared with the control group. Moreover, the effect of both the smoking and age on the level of adiponectin and antioxidants was studied. The results showed a significant decrease in the level of adiponectin and catalase in smoking diabetic patients compared to non-smokers. On the other hand, the study showed that there was a significant increase in the level of superoxide dismutase in smoking patients compared to non-smokers. As for the effect of age, the results showed a significant increase in superoxide dismutase with aging in patients with diabetes, while there was a significant decrease in the levels of both glutathione and vitamin C with aging.Keywords: Diabetes mellitus, Adiponectin, Antioxidants.